AB0092 Effect of methotrexate, leflunomide and hydroxychloroquine on the insulin resistance and obesity associated with rheumatoid arthritis: obese mouse models of rheumatoid arthritis. (15th June 2017) - Rosa, I Arias de la; Rodriguez-Cuenca, S; Jimenez-Gomez, Y; Ruiz-Limon, P; Perez-Sanchez, C; Abalos, MC; Collantes, E; Vidal-Puig, A; Escudero-Contreras, A; Lopez-Pedrera, C; Barbarroja, N
Abstract : Background: Numerous studies have demonstrated the closely association between rheumatoid arthritis (RA) and metabolic complications such as obesity and insulin resistance. Thus, there is an urgent need for the use of therapies targeting both the activity of the disease and such metabolic disorders. Nowadays, the conventional treatment of RA consists of disease-modifying antirheumatic drugs (DMARDs) in monotherapy or combined. Yet, its beneficial/negative effect on the metabolic complications associated with cardiovascular disease prominent in RA patients is still unravelled. Objectives: To analyze and compare the effects of methotrexate, leflunomide and hydroxychloroquine on the obesity and insulin resistance in an obese collagen-induced arthritis (CIA) mouse model. Methods: CIA was developed in obese and lean mice. 55 C57Bl/6 mice (4–5 weeks) were used. Forty-one mice were fed with high fat diet (60%) until reaching 30g (obese) (OB). Groups of study: 5 non-diseased lean mice, 9 CIA lean mice, 5 non-diseased OB mice, 9 OB-CIA mice, 9 OB-CIA mice treated with leflunomide (10 mg/kg daily), 9 OB-CIA mice treated with methotrexate (3mg/kg three times/week) and 9 OB-CIA mice treated with hydroxychloroquine (60 mg/kg daily) for 15 days. Mice were weighted and the number of total inflamed digits was recorded daily. After treatment, before 72 hours of termination, glucose tolerance test (GTT) was performed. Buffy coat, plasma and metabolic tissues (gonadal and inguinal adipose tissue, skeletal muscle and liver) were collected. Results: CIA obese mice developed the arthritis earlier and more severe (increased number of inflamed digits) compared with CIA lean mice. Regarding the progression of the disease, the three drugs significantly reduced the number of affected joints from the second day of treatment. However, after 15 days of treatment, the therapies more effective inhibiting the generation of inflamed digits were hydroxychloroquine and methotrexate. The development of RA in both obese and lean mice did not have effect on the body weight. Among the therapies used, only the hydroxychloroquine significantly reduced the body weight after 11 days of treatment. Glucose tolerance test revealed that the area under the curve was markedly smaller in OB-CIA mice after treatment with hydroxychloroquine compared to other treatments and OB-CIA mice untreated, suggesting an improvement of insulin sensitivity. Analysis on the metabolic tissues of these mice is currently ongoing in order to completely elucidate the effect of these therapies in the metabolic state. Conclusions: 1) Obesity accelerates the development and aggravates the outcome of the arthritis in CIA mice. 2) Among the three DMARDs administered, hydroxychloroquine promoted a beneficial effect on the metabolism of CIA obese mice, reducing body weight and improving the insulin sensitivity. These results suggest that hydroxychloroquine could be used as a valuable therapeutic strategy in RA patients to reduce the disease activity and ameliorate the metabolic complications associated. Acknowledgements: Funded by PI2013–0191, ISCIII-FIS (CP15/00158), RD16/0012/0015 and Roche Pharma S.A Disclosure of Interest: None declared